Creutzfeldt–Jakob Disease Presenting With Dizziness and Gaze-Evoked Nystagmus: A Case Report. Issue 7 (February 2016) - Choi, Yun-Ju; Kang, Kyung-Wook; Lee, Sae-Young; Kang, Seung-Ho; Lee, Seung-Han; Kim, Byeong C.
Abstract : Abstract: Sporadic Creutzfeldt–Jakob disease (CJD) is clinically characterized by rapidly progressive dementia combined with other cardinal symptoms, such as myoclonus, visual or cerebellar disturbances, extrapyramidal or pyramidal disturbance, and akinetic mutism. However, as an initial manifestation, focal neurologic deficits other than the aforementioned or nonspecific generalized symptoms may lead to a misdiagnosis or a delayed diagnosis. The authors report a case of 66-year-old male patient with sporadic CJD who had dizziness, gaze-evoked nystagmus (GEN), and other central eye signs (impaired smooth pursuit, saccadic dysmetria) as an initial manifestation without dementia. The central eye signs led us to perform brain magnetic resonance images, which showed abnormal cortical high-signal intensity in both the cerebral and cerebellar hemispheres including the vestibulocerebellum. We reached a presumptive diagnosis of CJD, but the findings did not meet diagnostic criteria for probable CJD at that time. Three weeks after the initial work-ups, the patient presented with typical neurological findings of CJD: rapidly progressive dementia, akinetic mutism, and myoclonus of the left arm. Cerebrospinal fluid was positive for 14-3-3 protein, and electroencephalography showed periodic sharp wave complexes. In this patient, GEN and other central eye signs provided diagnostic clues for CJD. These unusual neurological manifestations may help physicians have a thorough knowledge of early deficits of CJD. Abstract : Supplemental Digital Content is available in the text